Filling Some Blanks in a Divergent Approach to Gabosines: Enantioselective Synthesis of (–)‐Epiepoxydon, (+)‐Phyllostine, (–)‐Gabosine D, and (–)‐Gabosine E. Issue 21 (4th July 2016) - Fresneda, Miguel Ángel; Alibés, Ramon; Bayón, Pau; Figueredo, Marta
Abstract : The levorotatory enantiomers of gabosines D and E were synthesized through a divergent approach that could equally well be applied to the synthesis of the dextrorotatory enantiomers, which have been isolated from natural sources. The approach relies on an initial desymmetrization of p ‐methoxyphenol, followed by an enzymatic resolution that separately provides the two enantiomers of synthon3 . This versatile synthon can be further transformed into the diverse polyoxygenated cyclohexane target molecules. Key steps in the synthesis of (–)‐gabosines D and E from (4 R, 6 S )‐3 are the stereoselective hydroxymethylation at the α‐carbonyl position leading to (+)‐4, and the subsequent reagent‐controlled epoxidation of the carbon–carbon double bond. A branching in the sequence also allowed the synthesis of the anhydrogabosines (–)‐epiepoxydon and (+)‐phyllostine. Abstract : The levorotatory enantiomers of gabosines D and E were synthesized through a divergent approach that could equally well be applied to the synthesis of the dextrorotatory enantiomers. A branching in the sequence also allowed the synthesis of the anhydrogabosines (–)‐epiepoxydon and (+)‐phyllostine.